Co-silencing of ABA receptors (SlRCAR) reveals interactions between ABA and ethylene signaling during tomato fruit ripening. Issue 1 (5th June 2022) - Zou, Jian; Li, Ning; Hu, Nan; Tang, Ning; Cao, Haohao; Liu, Yudong; Chen, Jing; Jian, Wei; Gao, Yanqiang; Yang, Jun; Li, Zhengguo
Abstract: The ripening of fleshy fruits is highly dependent on the regulation of endogenous hormones, including ethylene, abscisic acid (ABA) and other phytohormones. However, the regulatory mechanism of ABA signaling and its interaction with ethylene signaling in fruit ripening are still unclear. In this study, multi-gene interference (RNAi) was applied to silence the ABA receptor genes in tomato for screening the specific receptors that mediate ABA signaling during fruit ripening. The results indicated that the ABA receptors, including SlRCAR9, SlRCAR12, SlRCAR11, and SlRCAR13, participate in the regulation of tomato fruit ripening. Comparative analysis showed that SlRCAR11 and SlRCAR13 play more important roles in mediating ABA signaling during tomato fruit ripening. Co-silencing of the four genes encoding these receptors could weaken the ethylene biosynthesis and signaling pathway at the early stage of tomato fruit ripening, leading to delayed fruit ripening. Meanwhile, co-silencing enhanced fruit firmness, and altered the shelf-life and susceptibility to Botrytis cinerea of the transgenic fruits. Furthermore, blocking ABA signaling did not affect the ability of ethylene to induce fruit ripening, whereas the block may inhibit the effectiveness of ABA in promoting fruit ripening. These results suggested that ABA signaling may be located upstream of ethylene signaling in regulating fruit ripening. Our findings provide a new insight into the complex regulatory network of phytohormones in regulating fruit ripening in tomato.